Evaluation of Physico-Mechanical Characteristics of Different Paddy Cultivars Grown in Humid Subtropical Region of Eastern China - Shakeel Ahmed Soomro; Kunjie Chen; Shakeel Hussain Chattha; Bakhtawar Wagan; Farman Ali Chandio; Fangfang Ji; Aamir Lund; Sohail Ahmed Soomro; Salauhddin Soomro (RADS Journal of Biological Research & Applied Science, 2023)
Background: Paddy during various stages i.e. loading, transportation, storage, handling etc. occurs severe losses, which can be reduced by designing appropriate post-harvest machineries using physico-mechanical properties.